The influence that hepatic cirrhosis provides in exercise capacity and muscle strength: a review - Renata Lopes Krüger; Bruno Costa Teixeira; Alexandre Simões Dias; Álvaro Reischak-Oliveira
AbstractIntroduction Hepatic cirrhosis leads to a series of physiological changes, among which stand out cardiorespiratory and muscle impairments. These changes determine a negative impact on quality of life and may cause physical inactivity.Objective The objective of this study was to review, in the most current scientific literature, the influence that hepatic cirrhosis provides in exercise capacity and muscle strength, and the effect of exercise when applied to this situation.Materials and methods For this review, research on original studies was carried out on Medical Literature Analysis and Retrieval System Online (assessed by PubMed), Scopus and Web of Science between the years 1990 to 2015. In order to be included, studies had to meet the following criteria: a) be from original articles; b) evaluate exercise capacity or muscle strength; and c) provide relevant results.Results and Discussion : The majority of studies concluded that the exercise capacity and muscle strength are decreased in individuals with cirrhosis when compared to control subjects.Final considerations Hepatic cirrhosis has negative effect on cardiorespiratory and neuromuscular capacity during physical exercise in individuals with liver disease.